Amphipod crustaceans from Chilean Patagonia - Coleman, Charles Oliver; Krapp-Schickel, Traudl; Häussermann, Vreni (European Journal of Taxonomy, 2022)
This paper describes new or little known Amphipoda collected from Hydrozoa, Bryozoa, Porifera or kelp along the Chilean fjord region. The following species have been found and most of them were redescribed and illustrated: Sunamphitoe femorata (Krøyer, 1845); Caprella cf. equilibra Say, 1818; Haplocheira barbimana robusta K.H. Barnard, 1932; Epimeria (Metepimeria) acanthurus (Schellenberg, 1931); Labriphimedia vespuccii K.H. Barnard, 1931; Leucothoe kawesqari Esquete & Aldea, 2015; Podocerus cf. danae (Stebbing, 1888); Ligulodactylus macrocheir (Schellenberg, 1926) and Torometopa cf. crassicornis (Schellenberg, 1931). One species in this contribution is new to science: Liouvillea rocagloria sp. nov.